"Organization for Cooperation": The Varieties and Vagaries of Labor at Rockefeller Center. Issue 2 (3rd July 2019) - Watson, Joseph M.
Abstract : In this article, I retell the history of Rockefeller Center, using questions of labor to introduce new dimensions to that well-known project. John D. Rockefeller, Jr., the project's patron, espoused cooperation between capital and labor. The Center's architects developed their own ideas about cooperation through a series of urban schemes and through their modes of practice. The process of design and construction, among other episodes in the project's development, made the possibilities and limitations of these cooperative ideals apparent. This re-evaluation of such a familiar work can encourage new thinking about how architectural historians and educators treat questions of collaboration.